2015
DOI: 10.15835/nbha4319708
|View full text |Cite
|
Sign up to set email alerts
|

Response of Durum Wheat Seedlings to Salinity

Abstract: Salinity is an important source of abiotic stress, limiting crop performance in most arid and semi-arid areas of the world. This research was conducted to determine the effects of salinity on physiological parameters of durum wheat (Triticum durum Desf.) genotypes. The research was conducted in the tissue culture laboratory at the Agriculture Faculty of Dicle University. The study consisted of one durum wheat commercial cultivar, five local cultivars and four advanced genotypes. There were three replications i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…These results agree with previous observations, which showed that osmotic stress and salinity in the immediate environment of germinating durum wheat seeds can delay or inhibit the germination process [41,42] and reduce the early seedling growth [43][44][45]. The use of a mannitol solution iso-osmotic to the NaCl solution allows to evaluate the relative contribution of the two components of the salt stress, namely the osmotic stress and the ion toxicity.…”
Section: Growth Performances Of Seedlings Grown Under Control Mannitol and Nacl Stress Conditionssupporting
confidence: 91%
“…These results agree with previous observations, which showed that osmotic stress and salinity in the immediate environment of germinating durum wheat seeds can delay or inhibit the germination process [41,42] and reduce the early seedling growth [43][44][45]. The use of a mannitol solution iso-osmotic to the NaCl solution allows to evaluate the relative contribution of the two components of the salt stress, namely the osmotic stress and the ion toxicity.…”
Section: Growth Performances Of Seedlings Grown Under Control Mannitol and Nacl Stress Conditionssupporting
confidence: 91%
“…Previously, root length and seedling growth of wheat cultivars were drastically reduced with increasing NaCl stress (Khatun et al, 2013). Yildirim et al (2015) noted that root length could serve as reliable criteria for determining the salinity tolerance of crops genotypes, as roots have direct contact with soil and are responsible for absorption of nutrients and water.…”
Section: Root Length (Cm)mentioning
confidence: 99%
“…Twenty seeds of each wheat genotype were planted in each petri dishes containing filter paper. Germination rate, seedling vigor, coleoptile length, root length and shoot length determined following the method of Yildirim et al [7]. Analysis of variance was performed using the Genstat statistic package.…”
Section: Methodsmentioning
confidence: 99%